Local Effects on Airway Inflammation and Systemic Uptake of 5 nm PEGylated and Citrated Gold Nanoparticles in Asthmatic Mice. Issue 10 (23rd December 2016) - Omlor, Albert J.; Le, Duc D.; Schlicker, Janine; Hannig, Matthias; Ewen, Raphael; Heck, Sebastian; Herr, Christian; Kraegeloh, Annette; Hein, Christina; Kautenburger, Ralf; Kickelbick, Guido; Bals, Robert; et al.
Abstract : Nanotechnology is showing promise in many medical applications such as drug delivery and hyperthermia. Nanoparticles administered to the respiratory tract cause local reactions and cross the blood–air barrier, thereby providing a means for easy systemic administration but also a potential source of toxicity. Little is known about how these effects are influenced by preexisting airway diseases such as asthma. Here, BALB/c mice are treated according to the ovalbumin (OVA) asthma protocol to promote allergic airway inflammation. Dispersions of polyethylene‐glycol‐coated (PEGylated) and citrate/tannic‐acid‐coated (citrated) 5 nm gold nanoparticles are applied intranasally to asthma and control groups, and (i) airway resistance and (ii) local tissue effects are measured as primary endpoints. Further, nanoparticle uptake into extrapulmonary organs is quantified by inductively coupled plasma mass spectrometry. The asthmatic precondition increases nanoparticle uptake. Moreover, systemic uptake is higher for PEGylated gold nanoparticles compared to citrated nanoparticles. Nanoparticles inhibit both inflammatory infiltrates and airway hyperreactivity, especially citrated gold nanoparticles. Although the antiinflammatory effects of gold nanoparticles might be of therapeutic benefit, systemic uptake and consequent adverse effects must be considered when designing and testing nanoparticle‐based asthma therapies. Abstract : When nanoparticles are applied via the respiratory tract, uptake to extrapulmonary organs is higher for PEGylated than citrated 5 nm gold nanoparticles. Asthma‐like inflammation of the respiratory system induces greater uptake of both nanoparticle types. The nanoparticles have an antiinflammatory effect in the airways, which is stronger for the citrated gold nanoparticles.